Luigi Nono: Texte, Studien zu seiner Musik - Nono, Luigi 1924-1990; Stenzl, Jürg 1942- (Zürich Atlantis, 1975)
This volume primarily contains the texts Nono wrote as essays and lectures, as introductions to individual works and as statements on current problems, as well as his recorded dialogues in German translation. In addition, the most important studies on Nono are included, among others by Helmut Lachenmann, Hans Werner Henze, Karl Amadeus Hartmann, Luigi Pestalozza and Jurg Stenzl. An appendix with a catalogue raisonné, a bibliography of Nono's writings, a Nono bibliography and a Nono discography rounds off this volume, which no one who is interested in the latest music can do without.
Includes index.
Bibliography and discography: p. 444-458.
Keywords: 20th Century (1901-2000); Music philosophy and esthetics; Music criticism; Composing